PENGARUH MEDIA KARTU DOMINO TERHADAP KEMAMPUAN HOTS PADA MATA PELAJARAN MATEMATIKA KELAS IV SEKOLAH DASAR - Pratama, Ria Agustin Setya Sakti; Alyani, Fitri (Universitas Bhinneka PGRI, 2024)
This study seeks to prove whether or not there is an influence of domino card media on higher order thinking abilities (HOTS) in Mathematics subjects in class IV elementary school. A quasi-experimental design employing a quantitative method was utilized. A posttest-only non-equivalent control group design was the research design applied. Class IV students, totaling 64, were the sample used in this research, divided into two classes: the experimental class and the control class. The method of data collecting uses saturated sampling. Data collection is carried out through test instruments that include HOTS indicators. Testing shows that there is an influence on students' higher order thinking skills (HOTS) between the control class and the experimental class. According to data analysis, it is proven that there is an influence of the implementation of domino cards on HOTS abilities in fourth grade elementary school mathematics lessons.